STUDI TENTANG IMPLEMENTASI DAN PEMAHAMAN NILAI-NILAI ADAT DALAM RAYO RUMAH GODANG PADA REMAJA DI KENEGERIAN SENTAJO KABUPATEN KUANTAN SINGINGI - ', Gustilianto; ', Zahirman; ', Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: In accordance with customary provisions required all public or adolescent from each tribe to go in or come to the house Godang, and follow all the stages that exist in Rayo home Godang, but especially young couple (teenagers) each tribal began to decline to assemble or bersilahturami Godang home or home for the feast kotonya Godang home or on the 2nd day of Eid Eid. Based on the above issue the writer take the title